Simulation The Effect of Spoiler on Aerodynamic for Sedan Car - Mohd Zin, Muhammad Zakie (Progress in Engineering Application and Technology, 2022)
Nowadays, aerodynamics in vehicles now play an important role. Aerodynamics affects vehicle performance by changing parameter such as lifting force and drag force, which play a major role in high speeds and fuel economy. Its main objectives are to reduce drag and wind noise while also minimising noise emission, as well as to prevent undesired lift forces and other causes of aerodynamic instability when travelling at high speeds. For the analysis, the model is created in SOLIDWORKS and then imported into Ansys Workbench and Fluid Flow (Fluent) for further analysis. There are one aerodynamic model that have been developed which is Sedan. To collect data on the drag coefficient and lift coefficient, this simulation was run at five different: 120 km/h, 140 km/h, 160 km/h, 180 km/h and 200 km/h. According to this simulation, spoilers have a significant impact on drag reduction and the prevention of undesired lift forces.